ATP-regulated potassium channels and voltage-gated calcium channels in pancreatic alpha and beta cells: similar functions but reciprocal effects on secretion. - Rorsman, P; Ramracheya, R; Rorsman, N; Zhang, Q (2014)
Closure of ATP-regulated K(+) channels (K(ATP) channels) plays a central role in glucose-stimulated insulin secretion in beta cells. K(ATP) channels are also highly expressed in glucagon-producing alpha cells, where their function remains unresolved. Under hypoglycaemic conditions, K(ATP) channels are open in alpha cells but their activity is low and only ~1% of that in beta cells. Like beta cells, alpha cells respond to hyperglycaemia with K(ATP) channel closure, membrane depolarisation and stimulation of action potential firing. Yet, hyperglycaemia reciprocally regulates glucagon (inhibition) and insulin secretion (stimulation). Here we discuss how this conundrum can be resolved and how reduced K(ATP) channel activity, via membrane depolarisation, paradoxically reduces alpha cell Ca(2+) entry and glucagon exocytosis. Finally, we consider whether the glucagon secretory defects associated with diabetes can be attributed to impaired K(ATP) channel regulation and discuss the potential for remedial pharmacological intervention using sulfonylureas.